2022
DOI: 10.1097/sla.0000000000005687
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Pancreaticoduodenectomy: Increased Adoption and Improved Outcomes

Abstract: Objective: To compare the rate of postoperative 30-day complications between laparoscopic pancreaticoduodenectomy (LPD) and robotic pancreaticoduodenectomy (RPD). Background: Previous studies suggest that minimally invasive pancreaticoduodenectomy (MI-PD)—either LPD or RPD—is noninferior to open pancreaticoduodenectomy in terms of operative outcomes. However, a direct comparison of the two minimally invasive approaches has not been rigorously performed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…This study agrees with the findings reported in the recent literature 1,4,6,7,10,24,25 . The median operative time was 7.8 h overall and was significantly longer in the late group than in the early group in this report, with median operative times of 8.4 versus 7.2 h. One possible contributing factor for the longer procedure is more cases of level II and III pancreatic mesopancreas dissections in the late group, because only level I mesopancreas dissections were done at our institute before 2018.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study agrees with the findings reported in the recent literature 1,4,6,7,10,24,25 . The median operative time was 7.8 h overall and was significantly longer in the late group than in the early group in this report, with median operative times of 8.4 versus 7.2 h. One possible contributing factor for the longer procedure is more cases of level II and III pancreatic mesopancreas dissections in the late group, because only level I mesopancreas dissections were done at our institute before 2018.…”
Section: Discussionsupporting
confidence: 91%
“…4,6,8,10,11,[14][15][16]24 A recent study by Khachfe et al comparing 885 RPDs and 655 LPDs concluded that RPD adoption had increased and was associated with decreased overall and serious complications and increased optimal outcomes. 25 The true Achilles' heel of RPD, the high operative costs and the "challenging…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening the titles and abstracts, 592 articles that did not meet the inclusion criteria were excluded, leaving 169 articles. After reading the complete text, applying inclusion/exclusion criteria, and assessing data integrity, a total of 18 articles were included, comprising 5985 patients (2553 in the RPD group and 3432 in the LPD group, respectively) 14‐31 . The literature screening process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…After reading the complete text, applying inclusion/exclusion criteria, and assessing data integrity, a total of 18 articles were included, comprising 5985 patients (2553 in the RPD group and 3432 in the LPD group, respectively). [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The literature screening process is shown in Figure 1. Finally, all included studies were of high quality, and their basic characteristics are presented in Table 1.…”
Section: Study Selection and Quality Assessmentmentioning
confidence: 99%